Student Learning Comparison Using the Song "Dear God" by Avenged Sevenfold to Improve Listening Skills - Silfi Wiladatus Solikhah; Nur Ngazizah Turohmah; Dwi Heriyanto (Journal on Education, 2023)
English is the main language of international communication and world organizations. With the development of information and communication technology, the world has leveled itself so that association is no longer limited by national borders. The 2013 curriculum recognizes the important role of English there are four important aspects of the English language that we should always understand this includes listening, speaking, writing, and reading. Hearing is not the same as listening. But to hear in English is to hear. Songs can also have a positive emotional effect on listeners. Students often say the words of the song when they sing it. It makes students understand the content of the song subconsciouslyThe purpose of this study was to determine the effectiveness of English songs in improving listening skills in ninth-grade Sultan Agung Srati Junior High School (MTS) in the 2022/2023 school year. In this study, researchers used quantitative research on ninth-grade classes that were taken as population and sample. There were 43 students taken as samples. Based on the results, the use of songs as a medium in teaching listening to ninth-grade students serves to improve listening skills compared to conventional methods.